Breaking bread : insurgent Black intellectual life - hooks, bell, 1952-; West, Cornel (New York ; London : Routledge, 2017)
"In this provocative and captivating dialogue, bell hooks and Cornel West come together to discuss the dilemmas, contradictions, and joys of Black intellectual life. The two friends and comrades in struggle talk, argue, and disagree about everything from community to capitalism in a series of intimate conversations that range from playful to probing to revelatory. In evoking the act of breaking bread, the book calls upon the various traditions of sharing that take place in domestic, secular, and sacred life where people come together to give themselves, to nurture life, to renew their spirits, sustain their hopes, and to make a lived politics of revolutionary struggle an ongoing practice. This 25th anniversary edition continues the dialogue with 'In Solidarity,' their 2016 conversation at the bell hooks Institute on racism, politics, popular culture, and the contemporary Black experience"--Provided by publisher.
1. Black men and women : partnership in the 1990s -- 2. Introduction to Cornel West -- 3. Cornel West interviewed by bell hook s-- 4. Introduction to bell hooks -- 6. bell hooks interviewed by Cornel West -- 6. Dialogue between bell hooks and Cornel West -- 7. Dialogue between bell hooks and Cornel West -- 8. The dilemma of the black intellectual by Cornel West -- 9. Black women intellectuals by bell hooks.
"First edition published by South End Press 1991"--Title page verso.
Includes bibliographical references.
Keywords: African American intellectuals; African American intellectuals -- Interviews; African Americans -- Intellectual life